Estimated glucose disposal rate mediates the association between Life’s Crucial 9 and congestive heart failure: a population-based study - Wang, Liping; Xu, Yaying; Chen, Lele; Zhang, Huifeng (Frontiers in Endocrinology, 2025)
BackgroundLife’s Crucial 9 (LC9) is the latest indicator of cardiovascular health (CVH), and the estimated glucose disposal rate (eGDR) is a non-invasive indicator of insulin resistance (IR). However, the relationships between LC9 and eGDR and congestive heart failure (CHF) remain unknown.MethodsIn this cross-sectional study, participants aged ≥20 years in the NHANES database from 2005 to 2018 were analyzed. Weighted linear regression, logistic regression, subgroup analysis, and restricted cubic spline (RCS) analysis were employed to analyze the associations among LC9, eGDR, and CHF. Mediation analysis was used to explore the mediating role of eGDR in the association between LC9 and CHF.ResultsA total of 22,699 adult participants were included, among whom 661 suffered from CHF. The mean age of the participants was 47.52 (0.26) years old, with 11186 (48.68%) males and 11513 (51.32%) females. The average value of LC9 was 71.16 (0.22), and that of eGDR was 7.91 (0.04). After adjusting for confounding factors, linear regression showed that LC9 was independently and positively associated with eGDR (β: 1.11, 95%CI: 1.07 - 1.14, P < 0.0001). Logistic regression indicated that both LC9 (OR: 0.76, 95%CI: 0.65 - 0.88, P < 0.001) and eGDR (OR: 0.81, 95%CI: 0.76 - 0.86, P < 0.0001) were independently and negatively associated with the prevalence of CHF. Mediation analysis revealed that the association between LC9 and CHF was mainly mediated by eGDR, with a proportion of 66%.ConclusionThis study suggests that higher LC9 scores and eGDR values imply a lower prevalence of CHF. Meanwhile, eGDR is the main intermediate factor in the association between LC9 and CHF, indicating that good CVH may reduce the prevalence of CHF by improving IR.